The Kajian Psikologi Keluarga: Benarkah Cinta adalah Unsur Terpenting dalam Pernikahan? - Rohmatul Hannani (PT. PENERBIT TIGA MUTIARA, 2023)
Love is the initial motivation for couples to decide to get married. However, love can change over the course of marriage. The pros and cons regarding the truth that love is the foundation and reason for the survival of a marriage need to be studied further. The importance of knowing the most important elements in marriage will minimize conflict and even divorce. The method used in this research is a descriptive qualitative method with data collection techniques based on literature studies. The study of marriage and all components of marriage is the object of this research. The main research data comes from the book